BUSINESS INTELLIGENCE FOR DETERMINING PROMOTIONAL MEDIA - Alvianingrum, Ante Wahyu; Sari, Dini Fakta; Syadziliy, Abil Hasan Ali Asy; Supriatin, Supriatin; Nur’aini, Nur’aini (Journal of Intelligent Software Systems, 2024)
Abstract—In 2021-2022, SMK Dirgantara Putra Bangsa experienced a decrease in the number of prospective students who registered. This condition encourages schools to innovate and be creative in choosing effective promotional media in disseminating information on New Student Admissions (PPDB) to the public widely and routinely, with the aim of attracting more new students. This promotional effort involves the use of various types of promotional media. Business intelligence plays a role in processing organizational data into useful information to improve performance, by analyzing historical data which is then used to support decision making and planning. The K-Means algorithm is one of the clustering methods that is often used because of its ease of implementation and its ability to minimize the sum of squared error (SSE) value between data and the specified centroid. The collaboration between Business Intelligence and K-Means clustering is expected to help SMK Dirgantara Putra Bangsa in choosing the right promotional media and creating new innovations in disseminating PPDB information to the public.Keywords— PPDB, Business intelligence, K-Means clustering, Media Promosi